Effect of crumb rubber on the punching shear behaviour of reinforced concrete slabs with openings. (13th December 2021) - Elsayed, Mahmoud; Tayeh, Bassam A.; Kamal, Doaa
Highlights: The workability of concrete mixtures decreases with increasing CR content. The mechanical properties of rubberised concrete decrease as CR content increases. Punching shear strength decreases with increasing CR content. Openings in flat slabs cause a significant reduction in punching shear strength. The use of CR and the presence of openings exert a negative influence on the stiffness. The use of 5% CR improves the toughness of the test specimens. Abstract: This study aims to evaluate the mechanical properties of concrete incorporated with crumb rubber (CR), i.e. rubberised concrete, and investigate the punching shear behaviour of rubberised concrete slabs with openings adjacent to columns. For this purpose, four concrete mixtures with different percentages (0%, 5%, 10% and 20%) of CR as volume replacement for fine aggregates were prepared. Twelve slabs were cast (i.e. three slabs for each mixture). One slab had no opening, the second slab had an opening with a size of 100×100 mm 2 and the third slab had an opening with a size of 150×150 mm 2 . Results showed that the use of CR exerted a negative effect on the mechanical properties of concrete. Meanwhile, the addition of up to 5% CR caused a slight reduction in the compressive strength, tensile strength and flexural strength of rubberised concrete. The experimental results indicated that the punching shear strength and stiffness of rubberised concrete slabs decreased with increasing CR. However, the toughness of the test specimens increased by using CR content up to 5% and then declined for 10% and 20% CR contents. Openings in flat slabs adjacent to the column face cause a significant reduction in punching shear strength, and punching shear strength decreases with an increase in opening size. Finally, the accuracy of four design code equations, namely ACI 318-2014, ECP 203, BS8110 and Euro -2 in predicting the punching strength of rubberised concrete slabs with or without openings is evaluated and compared with the experimental results.